Changing the Environmental Behaviour of Small Business Owners: The Business Case. (31st March 2015) - Walker, Beth; Redmond, Janice
Abstract: The importance of the environment is something of a cracked record to many small business owners, as historically any calls to business to change or improve their practices or behaviours were from the 'environmental' or 'green' perspective, rather than from a business perspective. As a consequence, many small businesses have simply tuned out. This research sought to identify the impact of an education intervention program that encouraged better environmental management practices and provided practical assistance to the businesses. The research was designed to test the effectiveness of the program and record any changes that occurred in the businesses over the duration of the project. To measure changes, it included a pre- and post-intervention survey. Overall, there was an increased awareness in most of the businesses in regard to environmental issues. Participants from many of the businesses also expressed positive changes to both behaviours and attitudes to environmental issues. This demonstrated the value of the program, and also highlighted the challenge to engage small business, even when a business case is apparent, given the cost of implementing this type of intensive and personalised assistance.